Granting Inheritance to Extramarital Children in the Perspective of Islamic Law - Khoyum, Adlian Aldita Alif Aisyah Ainur; Amilia, Bertha; Ardana, Candra Hafidz (Contemporary Issues on Interfaith Law and Society, 2023)
At present there are many cases of early marriage caused by a person getting pregnant before the legal marriage takes place. This incident encouraged the community to enter into legal marriages resulting in children born out of wedlock. While, in customary law if a woman gives birth to a child out of wedlock, the child will only have a civil relationship with the mother. The legal relationship that a child has only with his mother means that the child is not entitled to become the heir of his biological father's family. The purpose of this study was to determine the status of children outside of marriage according to Islamic law and marriage law in Indonesia. In addition, this study also aims to find out and analyze the position of the inheritance rights of children outside of marriage along with the distribution of inheritance rights to children outside of marriage when compared to their siblings who are children with legal marriages.